A host cell membrane microdomain is a critical factor for organelle discharge by Toxoplasma gondii. Issue 5 (October 2016) - Tahara, Michiru; Andrabi, Syed Bilal Ahmad; Matsubara, Ryuma; Aonuma, Hiroka; Nagamune, Kisaburo
Abstract: Host cell microdomains are involved in the attachment, entry, and replication of intracellular microbial pathogens. Entry into the host cell of Toxoplasma gondii and the subsequent survival of this protozoan parasite are tightly coupled with the proteins secreted from organelle called rhoptry. The rhoptry proteins are rapidly discharged into clusters of vesicles, called evacuoles, which are then delivered to parasitophorous vacuoles (PVs) or nucleus. In this study, we examined the roles of two host cell microdomain components, cholesterol and glycosylphosphatidylinositol (GPI), in evacuole formation. The acute depletion of cholesterol from the host cell plasma membrane blocked evacuole formation but not invasion. Whereas the lack of host cell GPI also altered evacuole formation but not invasion, instead inducing excess evacuole formation. The latter effect was not influenced by the evacuole-inhibiting effects of host cell cholesterol depletion, indicating the independent roles of host GPI and cholesterol in evacuole formation. In addition, the excess formation of evacuoles resulted in the enhanced recruitment of host mitochondria and endoplasmic reticulum to PVs, which in turn stimulated the growth of the parasite. Graphical abstract: Highlights: Roles of host microdomain components, cholesterol and GPI, in evacuole formation Host GPI was incorporated into evacuoles formed in host cell by T. gondii . The depletion of cholesterol blocked evacuole formation. The lack of GPI induced excess evacuole formation. The lack of GPI enhanced recruitment of host organelles and the parasite growth.